Longitudinal Analysis of the Absence of Intraoperative Neural Response Telemetry in Children using Cochlear Implants - Moura,Amanda Christina Gomes de (2014)
Introduction Currently the cochlear implant allows access to sounds in individuals with profound hearing loss. The objective methods used to verify the integrity of the cochlear device and the electrophysiologic response of users have noted these improvements. Objective To establish whether the evoked compound action potential of the auditory nerve can appear after electrical stimulation when it is absent intraoperatively. Methods The clinical records of children implanted with the Nucleus Freedom (Cochlear Ltd., Australia) (CI24RE) cochlear implant between January 2009 and January 2010 with at least 6 months of use were evaluated. The neural response telemetry (NRT) thresholds of electrodes 1, 6, 11, 16, and 22 during surgery and after at least 3 months of implant use were analyzed and correlated with etiology, length of auditory deprivation, and chronological age. These data were compared between a group of children exhibiting responses in all of the tested electrodes and a group of children who had at least one absent response. Results The sample was composed of clinical records of 51 children. From these, 21% (11) showed no NRT in at least one of the tested electrodes. After an average of 4.9 months of stimulation, the number of individuals exhibiting absent responses decreased from 21 to 11% (n = 6). Conclusion It is feasible that absent responses present after a period of electrical stimulation. In our sample, 45% (n = 5) of the patients with intraoperative absence exhibited a positive response after an average of 4.9 months of continued electrical stimulation.